ESTUDIOS CROMOSOMICOS EN ESPECIES DE HYPOCHAERIS L. (ASTERACEAE, LACTUCEAE) DE CHILE - Baeza, Carlos M.; Cabezas, Carolina; Terrab, Anass; Stuessy, Tod; Ruiz, Eduardo; Negritto, María; Urtubey, Estrella (Gayana Botánica, 2007)
The genus Hypochaeris (Asteraceae, Lactuceae) contains twelve species in Europe, three in Asia, and approximately 50 in South America. In this paper, we worked with mitotic chromosomes of three different species of Hypochaeris from Chile: H. acaulis, H. incana and H. scorzonerae. The species are very different in morphology and geographic distribution. The aim of this work was to compare the chromosome morphology of these species. We found that the chromosomes are different in size and morphology in H. acaulis (smaller than 6 µm and only chromosome 3 having a secondary constriction on the short arm). In H. incana and H. scorzonerae the chromosomes are very similar in size, and chromosomes 2 (on the long arm) and 3 (on the short arm) contain secondary constrictions. A tetraploid is reported for H. scorzonerae.